2022
DOI: 10.3389/fpsyg.2022.951309
|View full text |Cite
|
Sign up to set email alerts
|

Associations between adolescent students’ multiple domain task value-cost profiles and STEM aspirations

Abstract: According to the modern expectancy-value theory, students’ task values may differ across domains, manifesting as varying motivational patterns. In middle school, students’ motivation becomes increasingly apparent and may direct their future occupational aspirations. Using a person-oriented approach, this study examines students’ self-concept, and positive and negative task values (i.e., utility value, intrinsic value, and emotional cost) across Finnish language, math, biology, and physics, and the stability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Prior studies have identified profiles based on varying sets of EVT constructs: expectancies or self-concept only (e.g., Franzen et al, 2022;Umarji et al, 2018), a single value factor (e.g., Chow & Salmela-Aro, 2011;Franzen et al, 2022;Viljaranta et al, 2009), both (Lazarides et al, 2016), or a more multifaceted set of values and costs Lazarides et al, 2019Lazarides et al, , 2020Lazarides et al, , 2022Raufelder et al, 2022;Vinni-Laakso et al, 2022;Watt et al, 2019;. While many studies have focused on motivational patterns for one school subject at a time, mostly math Lazarides et al, 2019Lazarides et al, , 2020Lazarides et al, , 2022Watt et al, 2019;, the involvement of two or more subjects has revealed clear intraindividual hierarchies (i.e., subject-specific preferences) in some students' motivation.…”
Section: Motivational Profilesmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior studies have identified profiles based on varying sets of EVT constructs: expectancies or self-concept only (e.g., Franzen et al, 2022;Umarji et al, 2018), a single value factor (e.g., Chow & Salmela-Aro, 2011;Franzen et al, 2022;Viljaranta et al, 2009), both (Lazarides et al, 2016), or a more multifaceted set of values and costs Lazarides et al, 2019Lazarides et al, , 2020Lazarides et al, , 2022Raufelder et al, 2022;Vinni-Laakso et al, 2022;Watt et al, 2019;. While many studies have focused on motivational patterns for one school subject at a time, mostly math Lazarides et al, 2019Lazarides et al, , 2020Lazarides et al, , 2022Watt et al, 2019;, the involvement of two or more subjects has revealed clear intraindividual hierarchies (i.e., subject-specific preferences) in some students' motivation.…”
Section: Motivational Profilesmentioning
confidence: 99%
“…Another large group is usually formed by students with moderate motivation for all subjects (Franzen et al, 2022;Umarji et al, 2018;Vinni-Laakso et al, 2022). Overall low motivation groups have typically been among the smaller (Lazarides et al, 2016;Raufelder et al, 2022;Umarji et al, 2018;Viljaranta et al, 2009;Vinni-Laakso et al, 2022;see, however, Franzen et al, 2022). Notably, grouping based on a wider array of constructs has occasionally led to otherwise similar profiles that are most clearly differentiated by cost.…”
Section: Motivational Profilesmentioning
confidence: 99%
See 3 more Smart Citations